2023
DOI: 10.1108/ijem-03-2022-0095
|View full text |Cite
|
Sign up to set email alerts
|

Measuring teacher innovative behavior: a validated multidimensional inventory for use with public school teachers

Abstract: PurposeThe role of Teacher Innovative Behavior (TIB), in responding to systemic problems in educational systems and promoting “intrapreneurial” behavior has been recognized in recent times. A robust instrument that can help administrators and teacher educators gauge the levels of TIB among their teachers will facilitate the promotion of innovative behavior.Design/methodology/approachThis study tested a multidimensional innovative behavior inventory (IBI), innovation support inventory (ISI) and innovation outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Lebih lanjut, studi oleh Kuril et al (2023) menyoroti pengukuran perilaku inovatif guru dan dampaknya terhadap hasil pendidikan. Studi ini menggarisbawahi peran guru dalam membina keterampilan lintas-kurikuler dan menciptakan lingkungan yang kondusif untuk inovasi dalam lembaga pendidikan.…”
Section: Kajian Pustakaunclassified
“…Lebih lanjut, studi oleh Kuril et al (2023) menyoroti pengukuran perilaku inovatif guru dan dampaknya terhadap hasil pendidikan. Studi ini menggarisbawahi peran guru dalam membina keterampilan lintas-kurikuler dan menciptakan lingkungan yang kondusif untuk inovasi dalam lembaga pendidikan.…”
Section: Kajian Pustakaunclassified
“…Moreover, Yasir et al, (2023) indirectly showed in their research that learning orientation is one of IWB's dimensions in which individuals have the desire to learn new experiences, share knowledge, and improve their abilities. IWB also refers to an individual's ability to take the initiative in acting proactively to identify, solve problems, and persist in efforts to improve conditions (Ahmad et al, 2021;Kuril et al, 2023;Wolsink et al, 2019) and the ability to take calculated risks (Ahmad et al, 2021;Tu et al, 2019). More proactive and innovative behaviors will be needed to achieve excellent organizational performance in the Industrial Revolution 4.0 (Ali et al, 2021).…”
Section: Theoretical Reviewmentioning
confidence: 99%